The Development of the Central Business District (CBD) Based on Public-Private Partnership - Agus Sukoco; M Ikhsan Setiawan; Iswachyu Dhaniarti; Cholil Hasyim (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734)
This research aims to develop a model of the development of the Central Business District (CBD) based on Public-Private Partnership. Objective is (1) To design a development model Central Business District-based public-private partnership (public-private partnership) through case studies in Surabaya (Suramadu Surabaya side managed by Badan Pengembangan Wilayah Suramadu), (2) Develop a feasibility analysis of the technical-economical (feasibility study) the development of Business Central District-based public-private partnership (public-private partnership) in Surabaya (Suramadu Surabaya side) managed by the BadanPengembangan Wilayah Suramadu, by mapping, identification-evaluation of the obstacles encountered, opportunities and strategies and formulations can be developed. Lease (HGB) 30 year Rp.500.000 /m2/yr; Sales 80%; Sales price /m2Rp. 15,000,000 /m2 (up 10%/yr); Management & Rental Public Facility 5% of sales revenue. Based on the analysis of the feasibility of investment in the CBD area pessimistic conditions, showed decent results with NPV Rp. 7,152,755,613,547, IRR 14.34%, 1.37 PI and PBP 17 years.